Saturation Approach to Determine Grazing Mortality in Picoeukaryote and Synechococcus Populations - Stephen D. Archer; Laura C. Lubelczyk; Moriah Kunes; Moriah Kunes; Kathryn McPhee; Kathryn McPhee; Walter Dawydiak; Walter Dawydiak; Michael Staiger; Michael Staiger; Kevin M. Posman; Nicole J. Poulton (Frontiers in Marine Science, 2022)
A substantial component of phytoplankton production in the oceans is channeled through protistan grazers but understanding what dictates the magnitude of this process on a regional and temporal basis is limited, in part, by a shortage of experimental options. A novel saturation approach based on the functional response of planktonic grazers to increasing prey abundance was developed using laboratory cultures of the predator-prey combination of Ochromonas danica and Micromonas pusilla and tested in the coastal waters of the Gulf of Maine. In incubation series, 2 μm polystyrene microspheres were used as surrogate prey to generate increasing levels of saturation of predator ingestion rates of natural prey, resulting in increased rates of apparent growth of the picophytoplankton populations. The relationship between level of addition of surrogate prey to apparent growth, consistently provided significant estimates of maximal growth in the absence of grazing and grazing mortality for populations of picoeukaryotes and Synechococcus. Estimates of gross growth and grazing mortality were comparable to results from dilution experiments carried out in the same waters. The saturation approach represents an additional tool to investigate predator-prey interactions in planktonic communities. Further investigations may show that it can be used to quantify group-specific grazing mortality and growth rates beyond coastal waters and in multiple size classes of prey.